Restorative Justice dalam Tindak Pidana Narkotika pada Anak - I Komang Agus Muliawan; I Nyoman Gede Sugiartha; I Gusti Ayu Gita Pritayanti Dinar (Jurnal Analogi Hukum, 2022)
In considering the Juvenile Justice System Act No. 11 of 2012, keep in mind that children are the mandate and gift of Almighty God and have the dignity and value of humanity as a whole. Clarifying the problem in the study is an effort to apply restorative justice to the treatment and resolution of drug-related crimes, and to resolve the distractions of drug-related crimes in children. Restorative justice in the treatment and resolution of drug crimes committed by children and efforts to solve problems related to the use of diversion tactics in child drug crimes. The survey method used is a normative survey. The conclusion of the investigation is that the restorative justice approach generally does not work optimally in accordance with the provisions of Law No. 11 of 2012 on the juvenile justice system.